HUBUNGAN SALES SELF EFFICACY DENGAN KINERJA MENCAPAI TARGET PADA AVENGERS - Windar Ningsih; Yanladila Yeltas Putra (Jurnal Riset Psikologi, 2020)
The Relationship of sales self efficacy with the performance of achieving targets on the avengers. The purpose of this study was to determine the relationship between sales self efficacy and performance in achieving the target of the avengers in Plasa Telkom Bukittinggi. This research uses quantitative methods and research design is quantitative correlation.. The population in this study is all of the avengers in Plasa Telkom Bukittinggi. The research sample consisted of 28 people, with a total sampling technique. This study uses sales self efficacy scale and avengers target achievement data for July, August and September 2019. The data analysis technique used is product moment correlation. The results of this study show a correlation coefficient (r) of 0.487 and p=0.009 (p<0.01) which shows a positive relationship between sales self efficacy and performance in achieving the target of Avengers Plasa Telkom Bukittinggi.Hubungan sales self efficacy dengan kinerja mencapai target pada avengers. Tujuan dari penelitian ini untuk mengetahui hubungan antara sales self efficacy dengan kinerja dalam mencapai target pada avengers di Plasa Telkom Bukittinggi. Penelitian ini menggunakan metode kuantitatif dan desain penelitian adalah kuantitatif korelasi. Populasi pada penelitian adalah seluruh avengers di Plasa Telkom Bukittinggi. Sampel penelitian berjumlah 28 orang, dengan teknik total sampling. Penelitian ini menggunakan skala sales self efficacy dan data pencapaian target avengers bulan juli, agustus dan september 2019. Teknik analisis data yang digunakan adalah korelasi product moment. Hasil dari penelitian ini menunjukan koefisien korelasi (r) sebesar 0.487 dan p=0,009 (p<0,01) yang menunjukkan hubungan positif antara sales self efficacy dengan kinerja dalam mencapai target pada avengers Plasa Telkom Bukittinggi.